Association of Caribbean states : zone of cooperation (ACS Port of SpainTT, 2000)
Deals with topics such as Central America Economic Integration; strategic framework for vulnerability and disaster reduction in Central America; cultural exports and Caribbean development; port and shipping services in the Caribbean; ACS airlines face the challenges; TACA's experiences in strategic alliances; telecommunications in developments in the ACS region; the role of civil society in the integration process; CARIFESTA; and the Caribbean rum industry.
6th Ministerial Meeting December 2000